THE ROLE OF ISLAMIC RELIGIOUS EDUCATION TEACHERS IN E-LEARNING-BASED LEARNING TO DEVELOP SOCIAL TOLERANCE AND SOCIAL EMPATHY ATTITUDES IN HIGH SCHOOL STUDENTS - Anis Fuad; Ilzamuddin Ma'mur; Supardi; Wasehudin; Fitri Hilmiyati (Program Studi Pendidikan Agama Islam Fakultas Tarbiyah dan Keguruan UIN Sultan Maulana Hasanuddin Banten, 2026)
In Indonesia, which is rich in cultural, ethnic, and religious diversity, education plays an important role in building tolerance among the younger generation. In this context, Islamic religious education has a great responsibility not only to teach religious values, but also to instill an attitude of mutual respect and appreciation of differences among students. The purpose of this study is to find out the role of Islamic Religious Education teachers in developing social tolerance and social empathy attitudes in high school students at SMAN 1 Pontang and SMAN 1 Tirtayasa. This research uses a qualitative approach, which is a research approach that aims to understand social phenomena in depth and holistically through a descriptive data collection process. The results of this study are that the first implementation of PAI learning at SMAN 1 Pontang and SMAN 1 Tirtayasa has gone well, but it is not optimal in instilling the value of tolerance and social empathy. PAI teachers have tried to instill these values through lectures, discussions, real examples, and examples, but learning still focuses on the knowledge aspect. Second, the attitude of social tolerance of students in both schools shows a fairly good tendency, as seen from their ability to respect differences, work together in groups, and maintain harmonious relationships with peers. Third, the social empathy attitude of students as a whole is in the category of adequate, which is reflected in their ability to understand the feelings of friends, provide help when someone is experiencing difficulties, and show concern for the condition of the classroom environment. Fourth, PAI teachers are considered quite successful in developing students' social tolerance attitudes through exemplary attitudes shown in daily interactions, habituation of mutual respectful behavior, and the integration of tolerance values in materials and learning activities. Fifth, PAI teachers also showed success in fostering students' social empathy through a warm attitude, open communication, and delivery of material that emphasized the value of caring for others. Keywords: Empathy, PAI Teacher, Tolerance.